ENSURING ACCOUNTABILITY FOR THE JUNTA CRIMES AGAINST HUMANITY VIOLATION IN MYANMAR: USAGE OF THE ROME STATUTE AND POSSIBLE INVOLVEMENT OF THE UNSC VIA UNSCR REFERRAL - Mohamad Dafiryan (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
The objective of this journal article is to analyze as well as understand the scope of crimes that has been done by the recent Myanmar Juntas, specifically the crimes against humanity. It analyzes the determination of the crime based on the Rome Statute of the International Criminal Court as well as the possible applicability's-applicability applicability’ towards the ICC. The article will analyze the Junta action of using the basis of unfair election to enact crimes against humanity and the mechanism to bring the Juntas towards the ICC, either by UNSC Referral or the ICC investigation. In addition, the writer has also used several basis as a way to deem the current Junta government as illegitimate as well as the need to enact the UNSC referral.